An intervention aimed at reducing plagiarism in undergraduate nursing students. Issue 3 (May 2015) - Smedley, Alison; Crawford, Tonia; Cloete, Linda
Abstract: Plagiarism is a current and developing problem in the tertiary education sector where students access information and reproduce it as their own. It is identified as occurring in many tertiary level degrees including nursing and allied health profession degrees. Nursing specifically, is a profession where standards and ethics are required and honesty is paramount. The aim of this study was to evaluate the change in nursing student's knowledge and understanding of plagiarism before and after an educational intervention in their first semester of the Bachelor of nursing degree at a private college of higher education in Sydney, Australia. This study concluded that an educational intervention can increase knowledge and awareness of plagiarism among nursing students. Highlights: Review of the literature confirms that nursing students plagiarise as often as students in other disciplines. An educational intervention aimed as reducing the incidence of plagiarism is evaluated. Results show that educating students about academic honesty can reduce the incidence of plagiarism.